THEORETICAL ANALYSIS OF CENTRIFUGAL PUMP SELECTION BASED ON HYDRAULIC PARAMETERS FOR ENERGY EFFICIENT IRRIGATION SYSTEM - Rivanol Chadry; Mutiara Efendi; Rina, Rina; Rahmat Hafiz; Maheka Restu Araliz (International Journal of Social Science, 2025)
The efficiency of an irrigation system is strongly influenced by the proper selection of the water pump type, optimized according to the hydraulic requirements and comprehensive operational efficiency considerations. This study presents a theoretical analysis of centrifugal pump selection for paddy field irrigation systems, considering head losses, flow rate requirements, and power demand required to achieve optimal operational efficiency. Hydraulic equations and performance curves of commercially available centrifugal pumps were used to determine the most suitable pump configuration for the irrigation system’s operating conditions. The calculations encompass key parameters, including flow rate, flow velocity, total dynamic head, and pump power, to identify the most efficient pump type for irrigation applications. The analysis reveals that the selected centrifugal pump, operating at a discharge rate of 0.0056 m³/s and suction head variations between 3 and 10 m, yields a total head ranging from 4.7648 to 12.6627 m and a corresponding shaft power of 0.4745 to 1.4919 hp, with the efficiency maintained constant at 55%. The computational results demonstrate that variations in suction head are proportional to corresponding changes in total head and pump power. This theoretical approach offers a technical framework for selecting efficient and cost-effective centrifugal pumps suitable for small- to medium-scale agricultural irrigation systems. These findings underscore the significance of the theoretical approach as an efficient and cost-effective preliminary method for designing irrigation pump systems grounded in hydraulic analysis.